Accessibility of Online Advertising: A Content Analysis of Alternative Text for Banner Ad Images in Online Newspapers - Thompson, David; Wassmuth, Birgit (Disability Studies Quarterly, 2001)
This article reports a content analysis of newspaper practice regarding accessibility of online banner advertising. The researchers apply two techniques that may contribute to a greater understanding of online content: 1) an information location task that requires coding beyond the home page; and 2) coding the underlying structure of Web pages - the HTML Source code. This study provides evidence that three out of four (74.73 percent) banner ads found in online newspapers failed to present accessible content by using informative alternative text in the image tags of online banner ad images. For advertisers, that means millions of both sighted and blind online readers will not be exposed to their advertising messages. A simple solution for making online banner ads accessible is to add a few informative words of alternative text in the IMG tag of the Source code for the Web page.